prove the above PlZ help or I will fail in my assingmentss
Attachments:
![](https://hi-static.z-dn.net/files/de4/388e1172004954f4cd74471451994c20.jpg)
Answers
Answered by
0
Explanation:
Given that,
√( (1-sin∅)/(1+sin∅) ) = sec∅-tan∅
consider, LHS
√( (1-sin∅)/(1+sin∅) )
rationalise the denominator, we get
√( (1-sin∅)/(1+sin∅) × (1-sin∅)/(1-sin∅) )
⇒√( (1-sin∅)²/(1-sin²∅) ) (∵ (a-b)(a+b)=a²-b² )
⇒√( (1-sin∅)²/cos²∅ ) (∵ sin²∅+cos²∅=1⇒1-sin²∅=cos²∅)
⇒√( (1-sin∅)/cos∅ )²
⇒(1-sin∅)/cos∅
⇒1/cos∅ - sin∅/cos∅
⇒sec∅-tan∅ = RHS
∴Hence proved
HOPE THIS WOULD BE HELPFUL FOR YOU
Similar questions